Echocardiography of the intra-aortic balloon. Issue 10 (October 1975) - Weir, J; Yacoub, M; Pridie, R B
Abstract : Echocardiography was performed on 9 patients being treated for cardiogenic shock with an intra-aortic balloon. The value of simultaneous recording of the electrocardiogram, cardiac movements, and arterial pressure, with the echocardiogram of the intra-aortic balloon is discussed. The results indicate that echocardiography provides a method of studying intra-aortic balloon function.